2020
DOI: 10.3389/fnana.2020.00047
|View full text |Cite
|
Sign up to set email alerts
|

Activated Oxytocin Neurons in the PVN-DVC Pathway in Asthmatic Rats

Abstract: Asthma is a heterogeneous disease, and the central nervous system (CNS) also participates in the pathogenesis of asthma. We previously reported the amygdala might regulate asthmatic attacks via projecting to the paraventricular hypothalamic nucleus (PVN). The dorsal vagal complex (DVC) is a crucial region that modulates respiratory. This study aimed to observe the activity in both PVN and DVC and the connection between PVN and DVC in asthmatic rats. Immunohistochemistry was conducted to observe the changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Although neuronal projections between DMV cholinergic neurons and higher brain centers have been the subject of limited research, existing evidence suggests significant downstream projections from various brain areas to the NTS and DMV. These brain regions include the paraventricular nucleus of the hypothalamus, the central nucleus of the amygdala, and the bed nucleus of the stria terminalis [ 9 , 42 , 43 ], and they contain neurons like oxytocin and orexin neurons, among others, which may exert indirect effects on DMV cholinergic neurons [ [44] , [45] , [46] ]. To the best of our knowledge, our study is the first to demonstrate that the development of gastrointestinal dysfunction after stroke is closely related to the loss of cholinergic signaling in the DMV, resulting in vagal depression.…”
Section: Discussionmentioning
confidence: 99%
“…Although neuronal projections between DMV cholinergic neurons and higher brain centers have been the subject of limited research, existing evidence suggests significant downstream projections from various brain areas to the NTS and DMV. These brain regions include the paraventricular nucleus of the hypothalamus, the central nucleus of the amygdala, and the bed nucleus of the stria terminalis [ 9 , 42 , 43 ], and they contain neurons like oxytocin and orexin neurons, among others, which may exert indirect effects on DMV cholinergic neurons [ [44] , [45] , [46] ]. To the best of our knowledge, our study is the first to demonstrate that the development of gastrointestinal dysfunction after stroke is closely related to the loss of cholinergic signaling in the DMV, resulting in vagal depression.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with its specific receptor tyrosine kinase receptor B (TrkB), it induces phosphorylation at specific sites of the TrkB receptor and transmits BDNF signals to the nucleus for neuroprotection ( 55 ). The immediate-early genes c-fos and c-jun belong to a class of proto-oncogenes which can be induced by second messengers to respond quickly to external stimuli such as neurotransmitters, hormones, and nerve impulses ( 56 ). These genes express their expression products as third messengers to participate in the regulation of the transduction of signals closely related to learning and memory in cells ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was calculated that differences in the cAMP signaling pathway were associated with the differentiation of asthma subtypes, but further experiments are needed to verify whether this is consistent with the above-documented pathways. A study in rats concluded that oxytocin neurons in the paraventricular hypothalamic nucleus increased over time during an asthma attack (Chen et al, 2020). However, there was no further analysis of whether the oxytocin signaling pathway affects the asthma subtype.…”
Section: Discussionmentioning
confidence: 99%